1990
DOI: 10.1128/aem.56.7.2087-2092.1990
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens Is a Diazotrophic Bacterium

Abstract: This is the first report that Agrobacterium tumefaciens can fix nitrogen in a free-living condition as shown by its abilities to grow on nitrogen-free medium, reduce acetylene to ethylene, and incorporate '5N supplied as 1'5N2. As with most other well-characterized diazotrophic bacteria, the presence of NH4' in the medium and aerobic conditions repress nitrogen fixation by A. tumefaciens. The system requires molybdenum. No evidence for nodulation was found with pea, peanut, or soybean plants. Further understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The amplification of part of the nifH gene was also successfully carried out for Agrobacterium tumefaciens C58, which displayed a band corresponding to the fragment observed for E. cloacae. These results confirm at the molecular level recent reports on the diazotrophic status of A. tumefaciens C58 (18).…”
Section: Fgph273'supporting
confidence: 91%
“…The amplification of part of the nifH gene was also successfully carried out for Agrobacterium tumefaciens C58, which displayed a band corresponding to the fragment observed for E. cloacae. These results confirm at the molecular level recent reports on the diazotrophic status of A. tumefaciens C58 (18).…”
Section: Fgph273'supporting
confidence: 91%
“…This result is surprising since the DNA sequence of nifH is highly conserved among nitrogen-fixers (Ruvkun & Auzubel 1980;Normand et al 1988) and a Klebsiella pneumoniae nifHDK probe has frequently been used to detect homologous genes in very distant organisms. However, diazotrophic strains of Agrobacterium (Kanvinde & Sastry 1990) and of Methylosinus (Oakley & Murrel1988) were found to lack homology to the Klebsiella nif gene probe. It should be also noted that the bean isolates of group E formed symbiotically ineffective nodules on both P. vulgaris and L. leucocephala (Laguerre et al 1993;N.…”
Section: Comparison Of Populations Of Rhizobium 301mentioning
confidence: 99%
“…In this investigation, a structure resembles to root nodule often found in Leguminaceae plant roots was observed and assumed similar to typical nitrogen-fixing root nodules produced by Rhizobium sp. A few literatures reported that although A. tumefaciens is known as pathogenic bacterium for crown gall formation in roots, this bacterium was also found as similar to diazotrophs and report that A. tumefaciens can fix nitrogen and are capable of growing on nitrogen-free medium [47, 48]. However, the our finding is the first report as per current knowledge that shows A. tumefaciens can produce some sort of root nodules type structure with Vachellia pachyceras roots and have the ability to grow on nitrogen-free medium and reduce acetylene to ethylene at low level.…”
Section: Discussionmentioning
confidence: 99%